Mask Dance training's effect on children's confidence - Dwi Apriliyani (Universitas Pendidikan Indonesia, 2023)
Self-Confidence is an attitude in every individual who feels confident in his ability to act and is not easily influenced by others. People with self-confidence are optimistic, able to make their own decisions, and desire to achieve more. This program aimed to determine how to increase students' self-confidence through Mask Dance training at UPTD SD Negeri 2 Cantigi Kulon because self-confidence is a character value that students must have, especially in dancing. Data was collected using class action research, observation, and documentation methods. The students' confidence can be seen when students do not feel embarrassed when dancing in front of a crowd. This program aims to train children's mentality through Mask Dance activities for students in grades three to five. This program describes that students' self-confidence increases through memorizing dance moves and giving encouragement or motivation from the coach. Abstrak Kepercayaan diri (self-confidence) merupakan sikap pada setiap individu yang merasa percaya diri akan kemampuannya dalam melakukan suatu tindakan dan tidak mudah dipengaruhi oleh orang lain. Orang yang memiliki kepercayaan diri optimis, mampu membuat keputusan sendiri, dan keinginan untuk mencapai lebih banyak. Tujuan dari pengabdian ini adalah meningkatkan rasa percaya diri siswa melalui kegiatan menari Tari Topeng di UPTD SD Negeri 2 Cantigi Kulon karena kepercayaan diri merupakan nilai karakter yang perlu dimiliki oleh seorang siswa, terutama dalam menampilkan seni tari. Pengumpulan data dilakukan dengan metode tindakan kelas, observasi, dan dokumentasi. Rasa percaya diri siswa terlihat ketika siswa tidak merasa malu saat menari di depan orang banyak. Kegiatan yang dilakukan adalah melatih mental anak melalui kegiatan ekstrakurikuler Tari Topeng untuk siswa kelas tiga sampai kelas lima. Pengabdian ini memperlihatkan bahwa kepercayaan diri siswa meningkat melalui hafalan gerak tari dan pemberian dorongan atau motivasi dari pelatih. Kata Kunci: Kepercayaan diri; menari; mentalitas; siswa